2015
DOI: 10.1007/s11368-015-1193-4
|View full text |Cite
|
Sign up to set email alerts
|

Improve the prediction of soil bulk density by cokriging with predicted soil water content as auxiliary variable

Abstract: Purpose Soil bulk density (SBD) is a key soil physical property affecting the transport of water and solutes, which is essential to estimating soil carbon and nutrient reserves. However, it is considered to be time consuming, labor intensive, and expensive to obtain in situ SBD data. Therefore, it is important to estimate SBD at an acceptable level of accuracy using auxiliary variables with limited fieldmeasured data. Materials and methods The Heqing Dam agriculture area in Yunnan Province, Southwest China, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
5
22
0
Order By: Relevance
“…Our results agree with Chang et al (1998) and Yang et al (2016), who also found that cokriging was superior to kriging. Both COK P and COK PCA showed an improvement in the prediction of litter amount in comparison to OK.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results agree with Chang et al (1998) and Yang et al (2016), who also found that cokriging was superior to kriging. Both COK P and COK PCA showed an improvement in the prediction of litter amount in comparison to OK.…”
Section: Discussionsupporting
confidence: 92%
“…Basaran et al (2011) concluded that cokriging was superior to kriging in predicting soil hydraulic conductivity with limited available data on a 12.8 km 2 area. Yang et al (2016) found that cokriging improved the result by 45.5% compared with kriging, with soil bulk density as a primary variable and soil water content as an auxiliary variable. Yang et al (2016) found that cokriging improved the result by 45.5% compared with kriging, with soil bulk density as a primary variable and soil water content as an auxiliary variable.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These analyses are carried out using hybrid methods, such as co-kriging (Wen et al, 2015). The use of auxiliary variables normally increases the accuracy of the spatial predictions as observed in previous works (Stein and Corsten, 1991;Zhang et al, 1992;Yang et al, 2016b;Ceddia et al, 2015;Chen et al, 2016). Nevertheless, several works observed that the use of co-variates did not improve the accuracy of the interpolation (Martínez-Cob, 1996;Castrignano et al, 2011;Ceddia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Typical methods of measuring soil C/N ratio require data collection of SOC and TN, which can be considered a time-consuming and labor-intensive work that is not cost effective (Yang et al, 2016). Cokriging interpolation has been gradually applied to aspects of soil property prediction because it provides a higher accuracy of estimation, especially in the case of low sampling density, than the other method (Yao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%